The Effect of Life Review Therapy On The Level of Independence of Elderly at Panti Wredha St. Yoseph Kediri - Yoyok Febrijanto; Erva Elli Kristanti; Dian Taviyanda (Universitas STRADA Indonesia, 2020)
The purpose of this study was to determine the effect of life review on the level of independence of the elderly at Panti Wredha St. Joseph Kediri. The design used in this study was a pre-experimental one group pre-post test design. The study population was the elderly at Wredha St. Yoseph Kediri who met the inclusion criteria. The results showed that the level of independence before life review therapy with mild dependence was 11 respondents (68.8%) and after being given life review therapy with mild dependence was 10 (62.5%). Based on the Wilcoxon Sign Rank Test statistical test, it was obtained p 0.35 with a significance value of α <0.05. Based on the results, it can be concluded that there is an influence of life review therapy with the independence of the elderly at Panti Wredha St. Yoseph Kediri.